Implementasi Pendekatan Multikultural dalam Upaya Meningkatkan Kesadaran Kebhinekaan Menuju Masyarakat Madani - Wahyu Setyaningsih (IAIN Madura, 2021)
Globalization that happened in Indonesia bring into being the destroyed of cultural value. The multicultural of culture, social, and religion can not be avoided by Indonesian’s society. The one cause of many conflicts that happened in Indonesia is the weakness of understanding and meaningful about cultural ability. The awareness of multicultural in Indonesia did not buried in mind’s Indonesian citizen. The objectives of this article are 1. To know the general illustration about the Indonesian condition of age. 2. To know the strategies effort by multicultural approach to create the awareness of multicultural to concerned at civil society. 3. To know the effect of multicultural approach implementation to create the awareness of Indonesian multicultural. This article created by literature study like books, journals, and research report, news paper, and websites. The process of data analysis is done by descriptive. The process of written is created by the appropriate systematically from observation of problem until the recommendation of suggestion to continuing act. From the result of data analysis we can got the conclusion that multicultural approach implementation in increasing the multicultural awareness to become civil society will growth and develop the tolerances between one cultural with another cultural in Indonesian society so it can create civil society that is right and duty between human is same. Keywords: awareness of multicultural, approach multicultural and civil society.